Recognizing the Needs of Others: Municipal Candidates’ Intrinsic and Extrinsic Motivations to Support Immigrants and Religious Minorities - Scott, Colin; Medeiros, Mike (Frontiers in Political Science, 2021)
This research examines the influence of political candidates’ personality dispositions and constituency characteristics on their assessments of the needs of immigrants and religious minorities. Previous research, drawing on data from citizens, links personality differences to attitudes toward diversity and support for minority communities. Extending this research to candidates during an ongoing election campaign, this study examines the interaction between constituency diversity and politicians’ intrinsic motivations to recognize the interests of immigrants and religious minorities. Using data from a unique candidate survey during the 2018 municipal elections in two large Canadian provinces (N = 1,073), results show that personality traits provide an intrinsic motivation, independent of candidates’ descriptive characteristics or the level of diversity in their constituency, to recognize a higher level of support needed by members of these diverse communities. More agreeable candidates are consistently more likely to acknowledge that more should be done for immigrants and religious minorities whereas the negative influence of conscientiousness on minority recognition is suppressed in highly diverse constituencies. The results extend previous research on personality and intergroup dynamics and situate candidates’ recognition of the needs of others as an important antecedent to political representation.